Abciximab for thrombolysis during intracranial aneurysm coiling. - Gralla, J; Rennie, A; Corkill, R; Lalloo, S; Molyneux, A; Byrne, J; Kuker, W (2008)
INTRODUCTION: Thrombotic events are a common and severe complication of endovascular aneurysm treatment with significant impact on patients' outcome. This study evaluates risk factors for thrombus formation and assesses the efficacy and safety of abciximab for clot dissolution. MATERIALS AND METHODS: All patients treated with abciximab during (41 patients) or shortly after (22 patients) intracranial aneurysm coil embolisation were retrieved from the institutional database (2000 to 2007, 1,250 patients). Sixty-three patients (mean age, 55.3 years, +/- 12.8) had received either intra-arterial or intravenous abciximab. Risk factors for clot formation were assessed and the angiographic and clinical outcome evaluated. RESULTS: No aneurysm rupture occurred during or after abciximab application. The intra-procedural rate of total recanalisation was 68.3%. Thromboembolic complications were frequently found in aneurysms of the Acom complex and of the basilar artery, whilst internal carotid artery aneurysms were underrepresented. Two patients died of treatment-related intracranial haemorrhages into preexisting cerebral infarcts. Two patients developed a symptomatic groin haematoma. CONCLUSIONS: Abciximab is efficacious and safe for thrombolysis during and after endovascular intracranial aneurysm treatment in the absence of preexisting ischaemic stroke.